2010
DOI: 10.3390/molecules15106931
|View full text |Cite
|
Sign up to set email alerts
|

Prodigiosin Production by Serratia marcescens UCP 1549 Using Renewable-Resources as a Low Cost Substrate

Abstract: A new strain of Serratia marcescens UCP1459 isolated from a semi-arid soil produced the natural red pigment prodigiosin, characterized by an uncommon pyrrolylpyrromethane skeleton. Prodigiosin is a promising drug due to its reported antifungal, immunosuppressive and anti-proliferative activities. The objective of this work was to indentify a suitable medium to simultaneously enhance S. marcescens growth and pigment production using renewable resources obtained from industrial wastes. S. marcescens produced the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(59 citation statements)
references
References 20 publications
(30 reference statements)
1
52
1
1
Order By: Relevance
“…The molecular weight of the pigment was determined by using mass spectrometry which corresponding to 323.1 Da as shown in Figure S4 which agreed with the result obtained by [14].…”
Section: Mass Spectrum Of the Produced Prodigiosinsupporting
confidence: 83%
See 1 more Smart Citation
“…The molecular weight of the pigment was determined by using mass spectrometry which corresponding to 323.1 Da as shown in Figure S4 which agreed with the result obtained by [14].…”
Section: Mass Spectrum Of the Produced Prodigiosinsupporting
confidence: 83%
“…The molecular weight of the pigment was determined by using mass spectrometry by using model DSQ [14]. 7 …”
Section: Mass Spectrum Of Prodigiosinmentioning
confidence: 99%
“…On the other hand, our results show that, the supplementation of 20 % DPW broth with 1 % mannitol was more efficient in inducing prodigiosin production in P1 and fusant NRCF69 to (14.0 and 47.0 g L -1 , respectively). Casullo de Araújo et al (2010) recommended renewable resources obtained from industrial wastes (cassava wastewater) supplemented with mannitol to support the highest level of prodigiosin production (49.5 g L -1 ) using S. marcescens. Whereas Solé et al (1997) reported that glucose, maltose and other metabolizable sugar caused a reduction in prodigiosin due to catabolite repression or a decrease in pH observed in the cell suspensions, mannitol in the cultivation medium was a decisive factor in maintaining the pH at value of 7.0.…”
Section: Optimization Of Prodigiosin Productionmentioning
confidence: 99%
“…For instance, Starič et al (2010) reported that V. ruber DSM 14379 did not produce pigmentation at low (<15°C) and high temperatures (>43°C). Casullo de Araújo et al (2010) reported that high temperatures (over 30°C) affected the prodigiosin production in S. marcescens UCP 1549 , and the ideal temperature for pigment production was 28°C. They reported that the activity of one or more enzymes involved in prodigiosin synthesis is affected at high temperatures (Casullo de Araújo et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some other research groups reported that NaCl is required for growth and pigmentation in Serratia marcescens (Silverman and Munoz, 1973; Allen et al, 1983). Besides the impact of ion concentrations, the effect of the temperature on the activation of enzymes involved in prodigiosin biosynthetic pathway (Williams et al, 1971; Casullo de Araújo et al, 2010; Starič et al, 2010) has also been reported. However, most of the studies were related to room temperature or optimal temperature.…”
Section: Introductionmentioning
confidence: 99%